Pemanfaatan Instagram PT. Panasonic Gobel Indonesia - Syifa Reimita; Indri Rachmawati (UNISBA Press, 2023)
Abstract. This research entitled Utilization of Instagram PT. Panasonic Gobel Indonesia. (Case Study as Promotion of the Nanoe X Technology Program for Air Conditioning Products on Instagram @idpanasonic). PT. Panasonic Gobel Indonesia is a company engaged in technology. PT. Panasonic Gobel Indonesia is located in Jakarta. The main attraction of PT. Panasonic Gobel Indonesia is due to one of its promotional strategies through the Nanoe X program which is effective against the corona virus. This is considered to be an attraction as a promotional strategy because it is very adapted to the current situation in the midst of the Covid-19 pandemic. The purpose of this research is to find out how to use Instagram in the promotion strategy carried out by PT. Panasonic Gobel Indonesia (@idpanasonic). The method used in this study is a qualitative research method with a case study approach which aims to examine and analyze the promotion strategy carried out by PT. Panasonic Gobel Indonesia. The theory used in this study uses marketing mix theory. The data obtained in this study were through interviews and observations with the Corporate Communication Supervisor of PT. Panasonic Gobel Indonesia as the main informant was supplemented by a complementary informant from one of the consumers who used the